Optimal modelling of steel multi-span beams using the gradient-iterative method - Mikulski, Leszek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article describes the gradient-iterative optimization method and outlines the metod`s basic assumptions and illustrates its general use. The metod`s implementation was illustrated based on a steel I-beam. The described calculation example concerns the optimization of the height of the web of a multi-span beam. The method enables finding an optimal solution with the use of simple and commonly available software. To illustrate the effectiveness of the optimization method, multiple calculations were performed for beams with various spans and various load conditions.
Keywords: multi-span beam; structure optimization; gradient-iterative method; modern construction elements; belki wielkoprzęsłowe; optymalizacja konstrukcji; metoda iteracyjna; nowoczesne elementy konstrukcyjne